2008
DOI: 10.1152/ajprenal.90502.2008
|View full text |Cite
|
Sign up to set email alerts
|

Failure to upregulate the adenosine2Areceptor-epoxyeicosatrienoic acid pathway contributes to the development of hypertension in Dahl salt-sensitive rats

Abstract: Liclican EL, McGiff JC, Falck JR, Carroll MA. Failure to upregulate the adenosine2A receptor-epoxyeicosatrienoic acid pathway contributes to the development of hypertension in Dahl saltsensitive rats. Am J Physiol Renal Physiol 295: F1696 -F1704, 2008. First published October 1, 2008 doi:10.1152/ajprenal.90502.2008.-Adenosine-activated renovascular dilatation in Sprague-Dawley (SD) rats is mediated by stimulating adenosine2A receptors (A2AR), which is linked to epoxyeicosatrienoic acid (EET) synthesis. The A2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 43 publications
6
44
0
Order By: Relevance
“…In addition, we have previously demonstrated that the A 2A AR is upregulated in high-salt diet-fed mice compared with normal-salt diet-fed mice (51) and that failure to upregulate the A 2A AR-induced pathway contributes to the development of hypertension (44). Furthermore, a few studies have shown that the A 2B AR is selectively upregulated in ischemic mouse hearts and by hypoxic conditions (3,18) and that differential expression of ARs contributes to the functional heterogeneity of human endothelial cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have previously demonstrated that the A 2A AR is upregulated in high-salt diet-fed mice compared with normal-salt diet-fed mice (51) and that failure to upregulate the A 2A AR-induced pathway contributes to the development of hypertension (44). Furthermore, a few studies have shown that the A 2B AR is selectively upregulated in ischemic mouse hearts and by hypoxic conditions (3,18) and that differential expression of ARs contributes to the functional heterogeneity of human endothelial cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…Nonselective stimulation of P1 receptors with adenosine or selective stimulation of A2a subtype with DPMA induced consistent responses only in rats on an HS diet, possibly depending on enhanced generation of ADO [4,5] and/or on an increased expression ratio of A2R to A1R subtypes [5,6,7,12]. Presumably, on a high-salt intake, the vasodilator A2 prevails over the vasoconstrictor A1, whilst on a low-salt intake the effects of stimulation of both receptor types are in balance.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, a high-sodium (HS) intake was reported to increase the intrarenal generation of ADO [4,5] and the A2R/A1R expression ratio [5,6,7]. We found that exogenous ADO increased renal cortical and medullary perfusion in rats on HS but not on low-sodium (LS) diets [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these factors is almost certainly the hemoprotein cytochrome p450 metabolite arachidonic acid, which forms the signaling molecule epoxyeicosatrienoic acid (EET) (Liclican et al 2008). The role of EETs could be particularly important because, in addition to contributing to the maintenance of the basal tone and endothelium-dependent dilation of conduit arteries, it share many vascular protective properties with NO, suggesting that its alteration might be involved in the physiopathology of cardiovascular diseases.…”
Section: The Regulatory Role Of No Isoforms In Cerebrovascular Tonementioning
confidence: 99%